Applications of Exponential Function in Our Real Lives - Sah, Bikky; Mandal, Nitesh; Sahani, Suresh Kumar; Sahani, Kameshwar (International Journal of Humanities, Education, and Social Sciences, 2024)
This project delves into the real-life applications of exponential functions, analysing their significance in various fields. Through a comprehensive study, this project aims to provide insights into the practical implications of exponential functions and their role in modelling natural phenomena. This work is motivated by the works of [1-15,22].